Archéologies maghrébines et relectures de l’histoire. Autour de la patrimonialisation de Paul-Albert Février - Clémentine Gutron (L’Année du Maghreb)
This article examines the relationship between archeology, politics and historiography in the contemporary Maghreb from the standpoint of Paul-Albert Février. By analysing the professional path and work of the learned archaeologist and historian of late antiquity with the numerous political and academic reappropriations of his work by contemporary authors, this paper analyzes the question of history, its relationship to the past, its uses and the «need for history» in the Maghreb. The author points to the absence of a reflexive historiography in the study of North African antiquity, and sheds light on the difficulties encountered by the human sciences, today as yesterday, in addressing issues raised by those who, in a generation marked by the independence movements of the Maghreb, assumed the choice of a story that does not deny the reality of the present by enclosing themselves in a dead scholarship.